Preparation of an Index to a Book: A Case Study - Gopinath, M. A. (Journal of Information and Knowledge, 2002)
Describes how the organisation and the presentation of the text of the book can facilitate the preparation of the index concurrently with the press copy. Illustrates this with the two books of Ranganathan, the Prolegomena to library classification 3, and Ramanujan, the man and the mathematician. The choice of the ideas to be indexed has to be largely a matter of judgement and no rigid, objective principles can be formulated for it. The author’s approach to index is more exacting than that of the reader’s and it should be met. Therefore, the indexer should work in close touch with the author. Gives a set of rules helpful in the choice and rendering of the index term, and in the featuring and arrangement of the entries in the index. Describes the Work analysis, Job analysis, and the Routine involved in the preparation of the index.